Effects of moisture content, impulse polarity and earth electrode's dimension on dry and wet sand under high voltage conditions - Nor, N. Mohamad; Ramli, A. (JOHN WILEY & SONS LTD, 2008)
The study on the physics of discharges in soil and performance of earthing networks subjected to lightning Currents are important in order to improve the reliability of electrical systems and to obtain better electrical models of earthing systems. The soil characteristics of various moisture contents under high-impulse currents have been well studied in previous studies. In this present study, fast impulse generator is used to investigate the dry soil characteristics in two cylindrical test cells of different outer radii; 15 and 20 cm under high magnitude fast impulse conditions of both impulse polarities. This allows to study the characteristics of dry soil under high-impulse current conditions, and allows a comparison between the dry and wet soil characteristics under high-impulse conditions such as before and after breakdown of the test cell. In this study, the effects of impulse polarities, moisture content in soil and the outer dimensions of test cell on the soil characteristics under high-impulse currents were investigated. Copyright (c) 2007 John Wiley & Sons, Ltd.